(untitled) (Itinera, 2015)
To improvise means to be prepared for the unexpected, but since the unexpected is unforeseeable, we cannot be (fully) prepared. What is that status of this kind of knowledge? In answering the following question it is tempting to place improvisation within a range of unexplainable actions: something we may admire but cannot rationality clarify. In this article I will argue against such a view and, by analyzing cases of improvisation in jazz and in Argentinian tango, will underline two aspects of the rationality of the improvised conduct 1 the discipline required to acquire the improvisational habitus 2. The ability to exploit contextual affordances to generate coherent lines of improvisation. I will conclude that improvisation displays a form of rationality, albeit a form different from the instrumental rationality discussed in rational choice theory.